Deterring Abuse of the Financial System : Elements of an Emerging International Integrity Standard - Abbott, John (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2005)
Assessing financial systems' stability has required the IMF to dig deeper into financial sector issues and to include financial integrity elements in its assessments. Integrity elements are increasingly being addressed by international standards. More progress is needed, however, to prepare a comprehensive framework to prevent the abuse of the financial systems by both outsiders and insiders.